Optimization of the Stability of Nano-emulsion Medium Chain Triglycerides (MCT) using α-Cyclodextrin - Sagitha Fitri Novia; Vita Paramita; Hovivah Hovivah; Hermawan Dwi Ariyanto; Bambang Pramudono; Nanang Masruchin; Yoshii Hidefumi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
This study aims to determine the stability of nano-emulsion synthesized from virgin coconut oil (VCO) using α-cyclodextrin, and lecithin or tween 80 as surfactants. The study procedures included the production of nanoemulsions, examining emulsion type, density, particle size, pH, and zeta potential. The effect of the independent variables on the pH of the product was also examined using the response surface method (RSM). The results obtained 10 nano-emulsion formulas, belonging to the o/w type. The samples typically had a density range of 1.178–1.254 g/mL, with a pH of 5.0–5.5, which was considered safe for the skin. The smallest particle size of 5.495 µm was obtained from formula 6 (60 mL, 16 mL, 18 g, 6 g of water, VCO, cyclodextrin, and tween 80 as surfactant) with a zeta potential of -45.500 to -89.567 mV. Based on these results, formula 6 had the best characteristics, with an optimum pH of 5.5, small particle size, and good stability, as indicated by the zeta potential value.